2020
DOI: 10.1002/mrm.28410
|View full text |Cite
|
Sign up to set email alerts
|

Validation of T2‐based oxygen extraction fraction measurement with 15O positron emission tomography

Abstract: Purpose: To evaluate the accuracy of T 2-based whole-brain oxygen extraction fraction (OEF) estimation by comparing it with gold standard 15 O-PET measurements. Methods: Sixteen healthy adult subjects underwent MRI and 15 O-PET OEF measurements on the same day. On MRI, whole-brain OEF was quantified by T 2-relaxation-under-spin-tagging (TRUST) MRI, based on subject-specific hematocrit. The TRUST OEF was compared to the whole-brain averaged OEF produced by 15 O-PET. Agreement between TRUST and 15 O-PET whole-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 55 publications
(249 reference statements)
3
38
1
Order By: Relevance
“…The current study presents the first simultaneous comparison of OxFlow to 15 O-H2O and 15 O-O2 PET, and no significant differences were found between techniques. This agreement is in accordance with two recent studies comparing MR measurements of SvO2 to either PET or direct measures from the jugular blub (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…The current study presents the first simultaneous comparison of OxFlow to 15 O-H2O and 15 O-O2 PET, and no significant differences were found between techniques. This agreement is in accordance with two recent studies comparing MR measurements of SvO2 to either PET or direct measures from the jugular blub (25,26).…”
Section: Discussionsupporting
confidence: 92%
“…In this work, we used the TRUPC MRI technique to quantify OEF in two major cerebral veins: the SSS which drains the majority of cerebral cortical veins, the falx cerebri, meninges, diploic veins, and emissary veins; and the ICV which is formed by the unification of the thalamostriatal, septal, and choroidal veins and drains deep brain regions including thalami and basal ganglia. Among them, OEF at SSS has been shown to be correlated well with whole‐brain averaged OEF measured by 15 O‐PET 34 . We found that EtCO 2 correlated positively with PC‐based CBF but negatively with OEF at SSS, and there existed a negative correlation between OEF at SSS and CBF (both PC‐based and ASL‐based).…”
Section: Discussionsupporting
confidence: 53%
“…T 2 -based MR oximetry such as TRUST MRI has been exploited widely due to its non-invasive property, less model assumption, short scan time and high reproducibility (Lu and Ge, 2008;Lu et al, 2012;Xu et al, 2012;Jiang et al, 2018Jiang et al, , 2021. However, inconsistent results have been reported on whether OEF and CMRO 2 are increased, decreased or unaffected in sickle cell disease (Jordan et al, 2016;Bush et al, 2018bBush et al, , 2021Juttukonda et al, 2019Juttukonda et al, , 2020Li et al, 2020;Václavů et al, 2020;Prussien et al, 2021;Vu et al, 2021) The original bovine model was derived from bovine blood, which is thought to have similar magnetic properties as normal human blood (Lu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%